Biomarkers in skin autoimmunity-An update on localised scleroderma - Adrián Hernández‐Bustos; Begona Bolos; Kira Astakhova (Wiley, 2024)
Abstract Human autoimmune diseases are complex and highly diverse conditions that can be of localised or systemic nature. Understanding the basic biology of autoimmune diseases goes hand in hand with providing the clinics with valuable biomarkers for managing these diseases. The focus of this review is paid to localised scleroderma, an autoimmune disease affecting skin and subcutaneous tissue. Localised scleroderma has very few serological biomarkers for clinical analyses distinguishing it from main differentials, and yet noneffective prognostic biomarkers. With this regard, the review covers well‐established and new biomarkers such as cell surface proteins, autoantibodies and cytokines. In recent few years, several new biomarkers have been suggested, many provided with modern genomic studies. This includes epigenetic regulation of DNA, RNA transcriptomics and regulatory RNA such as microRNA and long non‐coding RNA. These findings can for the first time shed light on the genetic mechanisms behind the disease and contribute to improved diagnosis and treatment.